A new stem-coenagrionoid genus of damselflies (Odonata: Zygoptera) from mid-Cretaceous Burmese amber - Möstel, Claudia; Schorr, Martin; Bechly, Günter (Zootaxa, 2017)
A new genus and species of damselfly, Burmagrion marjanmatoki, gen. et sp. nov., is described from Early Cretaceous Burmese amber. It is attributed to the basal stem group of Coenagrionoidea. The inclusion of five wings from the same species suggests that the amber piece contains the remains of a mating pair of damselflies.